Activity of matrix metalloproteinase 2 and 9 isoforms in sputum samples from individuals infected with M. tuberculosis. (October 2019) - Baez, Irene Becerra; Sampieri, Clara Luz; Solano, Fernando Cruz; Martínez Cazares, María Teresa; Montero, Hilda; Cuevas, Roberto Zenteno
Abstract: M. tuberculosis stimulates matrix metalloproteinases secretion in the host; however, the patterns of matrix metalloproteinase 9 (MMP-9) and 2 (MMP-2) isoforms are unknown. Therefore, the aim of this study was to evaluate the activities of these isoforms in sputum samples of patients with varying degrees of mycobacterial load. Sputum samples were recovered from individuals with positive and negative diagnosis of tuberculosis. Bacillary load was determined by bacilloscopy, and presence and activity of MMP-2 and MMP-9 isoforms determined by gelatin zymography. Of the recovered samples; 39 were from individuals without tuberculosis and 48 with tuberculosis; 12 had low bacillary and 36 high bacillary load. Participation of MMP-2 isoforms were not observed, but in MMP-9, there was a decrease in the latent, associated with lipocalin and homodimeric isoforms. In contrast, there was a rise in the active isoform, all with statistical significance. In conclusion our results show that MMP-2 isoforms do not seems to be directly involved with tuberculosis evolution of infection. However, variations in MMP-9 isoforms were observed, which coincided with the progression of tuberculosis infection. These results raise questions regarding how MMP-9 isoforms might influence the formation and progression of granuloma, and their use as markers of progression of tuberculosis infection. Highlights: By gZ it was possible to quantify MMP-9 and MMP-2 isoforms in sputum samples. MMP-9 active was the only isoform that show increase with mycobacteria progression. No participation of MMP-2 isoforms were detected.